Sonoleaching development of a rapid determination of Pb from stabilized waste using ultrasound assisted leaching - Bellotindos, Luzvisminda Malli
This study develops an ultrasonic assisted leaching procedure, known as sonoleaching process for a fast determination of Pb form stabilized waste that could improve the Toxicity Characteristic Leaching Procedure (TCLP) of the United States Environmental Protection Agency (USEPA). The TCLP is a regulatory procedure which requires eighteen (18) hours of extraction for the determination of hazardous wastes/contaminants as to its toxicity charateristic. The results show that it improves this regulatory procedure by shortening the extraction time by 97.2%, decreasing the weight of waste to be used in the analysis by 95% and decreasing the volume of the extraction fluid used by 95%. The significant improvement in the TCLP is due to the application of ultrasound irradiation. Lead (Pb) is the major heavy metal selected in this study.